Reading Culture in Building Writing Practice Abilities among Writers of Lingkar Pena Forum Surabaya - Fardiana, Rizky Ayu (Palimpsest: Jurnal Ilmu Informasi dan Perpustakaan, 2020)
AbstractThe phenomenon of the emergence new writers in Indonesia provides its own unique view. This is inseparable from the development of writing trends. Interestingly, if the writer used to be dominated by adults who have long been in the world of authorship, now many emerging new writers originating from a reader. Most writers who begin writing have their roots in their habit of reading books. To develop a reading interest in writers, a supportive environment is needed, one of which is to follow the writing organization or community. Forum Lingkar Pena is an organization engaged in writing and reading. Forum Lingkar Pena activity that focuses on writing and reading helps new writers develop their writing skills. This qualitative study seeks to uncover the habit of reading and capital used by writers to develop writing skills. This study uses anethnographic method that centers on the activities of the authors in the Forum Lingkar Pena organization and uses snowball sampling techniques in determining its information, by conducting in-depth interviews with five informants who are writers of Forum Lingkar Pena. With the help of the theory of habitus and the production of capital belonging to Pierre Bourdieu, this study reveals how the capital obtained by the author in the realm is influenced by the reading habit they have. This study produced three types of writers, namely novice writer, intermediate writer and expert writer. In addition, researchers also found new findings that the habitus of reading certain readings will form writers to produce works similar to the reading they enjoy.Keywords: reading culture; habitus; capital production; writer; Forum Lingkar PenaAbstrakFenomena pertumbuhan penulis di Indonesia tidak terlepas dari adanya perkembangan tren menulis. Menariknya, jika dahulu penulis didominasi oleh kalangan yang telah lama berada di dunia kepenulisan, kini banyak bermunculan penulis-penulis baru yang berawal dari seorang pembaca. Sebagian besar penulis mengawali keinginan menulis dari kebiasaan membaca. Untuk mengembangkan kebiasaan membaca pada penulis, diperlukan peran aktif lingkungan terdekat seperti keluarga, lembaga pendidikan formal, maupun komunitas dan organisasi kepenulisan. Forum lingkar pena merupakan organisasi yang bergerak pada bidang menulis dan membaca. Kegiatan Forum Lingkar Pena berfokus pada literasi termasuk kegiatan menulis dan membaca dimana membantu penulis dalam mengembangkan kemampuan menulisnya. Studi kualitatif ini berusaha untuk mengungkap habitus membaca dan modal yang digunakan penulis untuk mengembangkan praktik menulis. Studi ini menggunakan metode etnografi yang terpusat pada aktifitas penulis dalam organisasi Forum Lingkar Pena dan menggunakan teknik snowball sampling dalam penentuan informannya, dengan melakukan wawancara mendalam terhadap lima informan yang merupakan penulis anggota Forum Lingkar Pena. Dengan dibantu teori habitus dan produksi modal milik Pierre Bourdieu, studi ini mengungkap modal yang didapatkan penulis dalam ranah dipengaruhi oleh habitus membaca penulis di masa lalu yang dipraktikkan kembali pada bentuk yang berbeda sesuai dengan kondisi sosial. Penelitian ini menghasilkan tiga tipe penulis, yaitu novice writer, intermediate writer dan expert writer.Kata kunci: budaya membaca; habitus; produksi modal; penulis; Forum Lingkar Pena